Wireless Carbon Monoxide Level Control and Monitoring System - Rerkratn, Apinai; Riewruja, Vanchai; Petchmaneelumka, Wandee; Tammaruckwattana, Sirichai (My University, 2025)
This paper proposes an online carbon monoxide control and monitoring system. The proposed system comprises an MQ-7 CO gas sensor module, a DHT11 digital temperature and humidity sensor module, an ESP8266 module, and a Relay Module. The ThingSpeak platform is used to create HMI for online monitoring of CO level, temperature, humidity, and status of the ventilation fan. This proposed system can measure CO and monitor all parameters of measurement data, alert users when CO values exceed the set value. In addition, the measured CO values are used to control the ventilation system operation (ON or OFF) to maintain the CO at a non-harmful level. The experiment testing and results with three conditions show that the proposed system can measure and monitor CO level, temperature, and humidity online with satisfying values. The ventilation fan can operate with function as a design procedure and maintain CO at a non-harmful level.
Keywords: Carbon Monoxide (CO); ESP8266; Internet of Things (IoT); MQ-7; Ventilation System